Why and how should the international volunteer tourism experience be improved? - Benson, Angela M. (Worldwide hospitality and tourism themes, 2015)
Gap year volunteering has grown in popularity in recent years but how do young people (and other age groups) choose between the many organizations that provide international volunteer tourism opportunities? This ebook is dedicated to the topic and specifically the quality of provision in this sector with its wide spectrum of operators from commercial to charitable organizations. It analyses the key issues and concerns and for identifying some of the ways in which the international volunteer tourism experience could be improved in-depth.